Markov and Semi-markov Chains, Processes, Systems and Emerging Related Fields - Vassiliou, Panagiotis-Christos; Georgiou, Andreas C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers a broad range of research results in the field of Markov and Semi-Markov chains, processes, systems and related emerging fields. The authors of the included research papers are well-known researchers in their field. The book presents the state-of-the-art and ideas for further research for theorists in the fields. Nonetheless, it also provides straightforwardly applicable results for diverse areas of practitioners.